Prospective Associations Between Sleep Disturbance and Repetitive Negative Thinking: The Mediating Roles of Focusing and Shifting Attentional Control. Issue 1 (January 2018) - Cox, Rebecca C.; Cole, David A.; Kramer, Eliza L.; Olatunji, Bunmi O.
Abstract: Although considerable evidence has linked sleep disturbance to symptoms of psychopathology, including repetitive negative thinking, few studies have examined how sleep disturbance may predict repetitive negative thinking over time. Further, no study to date has examined specific mechanisms that may account for this relationship. The present study sought to address these gaps in the literature by testing focusing and shifting attentional control as two potential mediators of the relationship between sleep disturbance and repetitive negative thinking over a 6-month period. A final sample of 445 unselected community participants completed measures of sleep disturbance and repetitive negative thinking at Time 1, measures of focusing and shifting attentional control 3 months later, and measures of repetitive negative thinking again 6 months later. Results revealed that focusing, but not shifting, attentional control mediated the relationship between sleep disturbance and repetitive negative thinking, specifically, worry, rumination, and obsessions. These findings provide preliminary evidence for focusing attentional control as a candidate mechanism that may explain the causal role of sleep disturbance in the development of repetitive negative thinking observed in various disorders. Highlights: Sleep disturbance predicts repetitive negative thinking over 6 months The effect is mediated by focusing attentional control Shifting attentional control is not a mediator